The Effectiveness of Cognitive Behavioral Therapy (CBT) in Reducing Addiction Severity and Craving and Improving Emotional Regulation in Individuals with Substance Use Disorder: A Quasi-Experimental Study - Ghiyasi Nejad , Saleh; Amiri Domari, Somayeh (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to examine the effectiveness of cognitive behavioral therapy in reducing addiction severity and substance craving and improving emotional regulation among individuals with substance use disorder. This study was conducted using a quasi-experimental design with a pretest–posttest structure and a control group. The statistical population included individuals with substance use disorder who referred to addiction treatment centers in Tehran in 2025. Using convenience sampling, 40 eligible participants were selected and randomly assigned to an experimental group and a control group, with 20 participants in each group. The experimental group received cognitive behavioral therapy in 10 sessions of 90 minutes, while the control group received no psychological intervention during the study period. Data were collected using the Addiction Severity Index, the Substance Craving Questionnaire, and the Difficulties in Emotion Regulation Scale. Data were analyzed using multivariate analysis of covariance. The results of ANCOVA showed that, after controlling for pretest scores, there was a statistically significant difference between the experimental and control groups in addiction severity, F(1, 37) = 54.36, p < 0.001, partial η² = 0.595, substance craving, F(1, 37) = 72.22, p < 0.001, partial η² = 0.661, and emotional regulation difficulties, F(1, 37) = 63.12, p < 0.001, partial η² = 0.630. These findings indicated that CBT significantly reduced addiction severity and substance craving and improved emotional regulation in the experimental group compared with the control group. The findings suggest that cognitive behavioral therapy can be considered an effective psychological intervention for individuals with substance use disorder. By targeting maladaptive thoughts, craving-related beliefs, emotional triggers, and ineffective coping patterns, CBT may help reduce addiction-related problems and strengthen emotional regulation capacity. Therefore, integrating CBT into addiction treatment programs may improve treatment outcomes and support relapse prevention.